Influence of different arbuscular mycorrhizal fungi isolates in enhancing growth, phosphorus uptake and grain yield of soybean in a phosphorus deficient soil under field conditions - Adeyemi, Nurudeen Olatunbosun; Atayese, Mufutau Olaoye; Sakariyawo, Olalekan Suleiman; Azeez, Jamiu Oladipupo; Olubode, Adebanke Ayooluwa; Ridwan, Mudathir; Adebiyi, Ademola; Oni, Olanrewaju; Ibrahim, Ifeoluwa (Communications in Soil Science and Plant Analysis, 2021)
A field experiment was conducted during two consecutive growing seasons (2017 and 2018) to evaluate the effects of inoculations with arbuscular mycorrhizal fungi (AMF) (Funneliformis mosseae, Rhizophagus intraradices and Claroideoglomus etunicatum) and phosphorus (P) fertilization (40 kg P 2 O 5 ha −1 ) on the growth, yield and P use efficiency (PUE) of two soybean (Glycine max L.) cultivars under low soil P (6 mg kg −1 ) condition. AMF inoculation promotes the growth of soybean to some level compared to the P fertilized plot; however, inoculation (~960 spores per 100 g of soil) of R. intraradices or F. mosseae increased the number of nodules, nodule dry weight, shoot dry weight, root dry weight, number of pods, 100-seed weight and seed yield in both TGx 1440-1E and TGx 1448-2E soybean cultivars compared to C. etunicatum and the control. The P uptake in the shoot and grain in both cultivars increased with AMF inoculations in the order R. intraradices > F. mosseae > C. etunicatum. The studies showed that the highest yield response (44.2- 45.4%) and (44.9- 46.5%) over the control was revealed by the inoculation with R. intraradices and F. mosseae inoculants, respectively, in both soybean cultivars. TGx 1448-2E variety was more tolerant to low soil P availability and had higher root nodulation, seed yield and PUE than TGx 1448-2E variety. The results confirm functional variation among the three AMF isolates tested, which is crucial in establishing potential formulation of AMF inoculants to enhance soybean productivity in P-deficient soils.